2017
DOI: 10.1136/oemed-2016-104015
|View full text |Cite
|
Sign up to set email alerts
|

Can work make you mentally ill? A systematic meta-review of work-related risk factors for common mental health problems

Abstract: It has been suggested that certain types of work may increase the risk of common mental disorders, but the exact nature of the relationship has been contentious. The aim of this paper is to conduct the first comprehensive systematic meta-review of the evidence linking work to the development of common mental health problems, specifically depression, anxiety and/or work-related stress and to consider how the risk factors identified may relate to each other. MEDLINE, PsychInfo, Embase, the Cochrane Collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
416
1
29

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 559 publications
(506 citation statements)
references
References 60 publications
19
416
1
29
Order By: Relevance
“…Yet, in a systematic review study, he identified that psychological harassment, high demands and low labor control, imbalance in work environment between effort and reward, low relational and procedural justice, stress, and poor social support in the workplace present as risk factors for depression, anxiety, and work-related stress (34) . The risk factors listed can be identified in the work of the public servant, where in spite of the stability of employment, they experience shortages of human and material resources, causing overload and accumulation of functions, bureaucratic and hierarchical management, as well as uncertainties regarding the transition of governments (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in a systematic review study, he identified that psychological harassment, high demands and low labor control, imbalance in work environment between effort and reward, low relational and procedural justice, stress, and poor social support in the workplace present as risk factors for depression, anxiety, and work-related stress (34) . The risk factors listed can be identified in the work of the public servant, where in spite of the stability of employment, they experience shortages of human and material resources, causing overload and accumulation of functions, bureaucratic and hierarchical management, as well as uncertainties regarding the transition of governments (35) .…”
Section: Discussionmentioning
confidence: 99%
“…Workplaces are an integral setting for improving health (Black and Frost 2011), and workplace-health-based interventions have been shown to reduce the burden of illness to both employees and the employer. Furthermore, it is often assumed that mental health problems only develop outside of the workplace and are not the responsibility of the employer, but there is growing evidence that poor psychosocial working conditions, commonly referred to as "job stressors," can increase the risk for developing symptoms, including depression, anxiety, burnout, and distress (Harvey et al 2017;Joyce et al 2016). Offering wellbeing intervention to staff such as the Tai Chi practice described in this study goes some way in offering an effective way to address these ongoing concerns.…”
Section: Creating a Positive Workplacementioning
confidence: 99%
“…A total of 42 questions were developed, which covered the following topics: perceived vulnerability, attitude towards employment, the psychosocial work environment, relationship with employer, coping style at work and response to symptoms. The choice of which psychosocial work risk factors to include was informed by a systematic review on this topic, which our research team was conducting at the same time 26. The selections of the other domains covered were based on a series of conversations with colleagues familiar with each topic area.…”
Section: Methodsmentioning
confidence: 99%